Antibacterial Activity of Honey on Staphylococcus aureus Isolated from Wounds - Shrestha, Anima; Kandel, Milan (Nepal Journal of Science and Technology, 2020)
Honey, a natural product of bees, has been used as nutritious food as well as medicine in ancient time for treatment of wound and burns. It has a healing property and is also very useful in the treatment of infection caused by antibiotic-resistant bacteria. The study was carried out to compare the antibacterial activity of three different honey obtained from Apis mellifera, A.serena and A.dorsata The study period was from February to June 2010. Fifty-two wound swabs were obtained from private clinics and hospitals. Laboratory work was done in Microbiology laboratory of St. Xavier’s College, Kathmandu, Nepal. Antibacterial activity of honey samples on 38 isolates of S. aureus showed that honey obtained from wild species A. dorsata was the most effective among the honey tested.